2017
DOI: 10.1080/14767058.2017.1400003
|View full text |Cite|
|
Sign up to set email alerts
|

The uterine leiomyoma and placenta previa: a meta-analysis

Abstract: We showed based on reports in observational studies that uterine leiomyoma is a risk factor for placenta previa in studies adjusted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 18 publications
0
7
0
3
Order By: Relevance
“…Studies have shown an increased risk of having placenta previa in cases of fibroid uterus in pregnancy [ 3 , 4 , 9 , 10 ]. One of the studies mentioned that uterine leiomyoma of size 5 cm or more increases the risk of placenta previa by 3.53-fold [ 11 ]. However, there is no mention of the types of fibroid typically involved in abnormal placentation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown an increased risk of having placenta previa in cases of fibroid uterus in pregnancy [ 3 , 4 , 9 , 10 ]. One of the studies mentioned that uterine leiomyoma of size 5 cm or more increases the risk of placenta previa by 3.53-fold [ 11 ]. However, there is no mention of the types of fibroid typically involved in abnormal placentation.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that endometrial receptivity is altered in women who smoke, and could explain previa implantation in spontaneous pregnancies in primigravidae. Other risk factors that may have an impact on the site of implantation include uterine leiomyoma (AOR 2.21; 95%CI: 1.48, 2.94) [26] and endometrial thickness [21].…”
Section: Low-lying Placenta and Placenta Previamentioning
confidence: 99%
“…Smatra se da je pojava intrauterinog zastoja u rastu ploda češća u trudnoćama u kojima je insercija placente na mestu postojanja mioma materice, što može uzrokovati poremećaj perfuzije placente [20].…”
Section: Komplikacije Mioma Tokom Trudnoće I Porođajaunclassified
“…It is believed that the occurrence of intrauterine fetal growth restriction is more common in pregnancies where the placental insertion is at the site of uterine myoma(s), which may result in the disruption of placental perfusion [20].…”
Section: Komplikacije Mioma Tokom Trudnoće I Porođajamentioning
confidence: 99%